2009
DOI: 10.3892/ijo_00000286
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the receptor for hyaluronan-mediated motility, correlates with expression of microtubule-associated protein in human oral squamous cell carcinomas

Abstract: Abstract. Receptor for hyaluronan-mediated motility (RHAMM) has previously been characterized as a cell surface receptor for hyaluronan and a microtubuleassociated intracellular hyaluronan binding protein. We examined the expression of RHAMM mRNA in 43 oral squamous cell carcinomas (SCCs) and 7 normal gingivae by real-time RT-PCR. The expression level of RHAMM mRNA was significantly higher in oral SCCs than normal gingivae (P=0.0047). Forty out of 43 oral SCCs showed expression of RHAMM splice variant (48 bp d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…TPX2 was initially reported to be a Xenopus microtubule-associated protein (27). TPX2 is a cell cycle protein and serves a key role in the stability of the mitotic spindle (18).…”
Section: Discussionmentioning
confidence: 99%
“…TPX2 was initially reported to be a Xenopus microtubule-associated protein (27). TPX2 is a cell cycle protein and serves a key role in the stability of the mitotic spindle (18).…”
Section: Discussionmentioning
confidence: 99%
“…TPX2 was found to be upregulated in squamous cell carcinoma of the lung with the expression correlating to tumor grade, stage and nodal status (4). The high-expression of TPX2 has been demonstrated in other cancers such as ovarian cancer (10) breast cancer (5) pancreatic cancer (11), meningioma (12), astrocytoma (13), mantle cell lymphoma (14), hepatocellular carcinoma (15), oral squamous cellcarcinomas (16), and giant-cell tumor of the bone (17). The high-expression of TPX2 has predictive value for the biological behavior of the disease, and can be used as a prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified that RHAMM was overexpressed in oral squamous cell carcinomas. 22 The overexpression of RHAMM has also been observed in other types of cancers. [23][24][25] In oral squamous cell carcinomas, RHAMM expression was correlated with the expression of TPX2 (targeting protein for X. laevis kinesinlike protein 2), encoding a protein which is required for the formation of microtubules at kinetochores in mammalian cells.…”
mentioning
confidence: 99%